2021
DOI: 10.3389/fanim.2021.784376
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Comparison During Chronic Heat Stress in Large White and Creole Pigs Using Image-Analysis

Abstract: Behavior is a good indicator of animal welfare, especially in challenging environments. However, few studies have investigated how pig behavior changes during heat stress. The current study is a proof-of-concept using Convolutional Neural Network (CNN) models to monitor pig behavior in order to investigate the differences in behavioral response to heat stress of two contrasted breeds: Large White (LW), selected for high performance, and Creole (CR), adapted to tropical conditions. A total of 6 slaughter pigs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…The use of postural and activity budgets is rarely described in the literature [however, see ( 60 63 )]. There are many studies of postural changes assessed by scan sampling and rare continuous analyses of behavior over more than 1 day.…”
Section: Discussionmentioning
confidence: 99%
“…The use of postural and activity budgets is rarely described in the literature [however, see ( 60 63 )]. There are many studies of postural changes assessed by scan sampling and rare continuous analyses of behavior over more than 1 day.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of pigs, Bonneau et al [75] reported an increase in the amount of time the animals were lying down on the side-to dissipate heat by contact with cool surfaces-by up to 5.9% when the temperature increased by 1 • C. The authors also determined that creole pigs (dark skin) spent more time lying down than large white pigs (lighter skin) (4%), probably due to the anatomical differences between breeds, which could help to identify heat-tolerant breeds for certain pig production units where ambient temperatures are high. In small-tail Han sheep raised indoors without climate control, Li et al [76] observed that ewe and ram lying behavior increased according to the THI increase (up to 45.10 ± 2.42%).…”
Section: Physiological Responses To Mitigate Heat Stressmentioning
confidence: 99%
“…Utilizing video sensors, PLF methods have been proven to be efficient, noninvasive, and stress-free, which allows continuous, real-time, and automated monitoring of animals to assist farmers in managing their livestock and improving their productivity. Considering these benefits, some studies [37][38][39][40][41][42][43][44] have leveraged PLF methods with video data to recognize pigs' behaviors relevant to their research. Table 1 summarizes some of the recent studies related to pig behavior recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers, such as Nasirahmadi et al [37], used traditional machine learning techniques because they need less data to train the model and are less computationally demanding. Meanwhile, others [38][39][40][41][42][43][44] used deep learning techniques since they can automatically extract more relevant features (instead of relying on handcrafted features), which improves performance. Before performing behavior recognition, some of the aforementioned studies used predefined bounding boxes and cropped images to localize pigs for validating their approach in recognizing individual postures in commercial farms [37] and providing a low-cost solution to monitor the aggressive behavior [40] as well as feeding and drinking behaviors [44] of individual pigs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation